METABOLIC SYNDROME RISK FACTORS IN INDIVIDUALS REFERRED TO A FAMILY HEALTH CENTER - (:unkn) unknown (PAKISTAN CARDIAC SOC, 2019)
Objective: To determine the prevalence and risk factors of metabolic syndrome in adults in accordance with the diagnosis criteria determined by International Diabetes Foundation (IDF). Methodology: A descriptive study was conducted with 201 individuals who were referred to a family health center in Istanbul in Turkey owing to any health problem. Percentage, mean, frequency and chi-square were used for statistical evaluation. Statistical significance was taken as p <0.05. Results: The mean age of the individuals participating in the study was 58.5 +/- 2, 49.3% were female and 50.7% were male. Average body mass index of individuals was 26.3 +/- 5, average LDL value was 126.12 +/- 37, average triglyceride was 169.9 +/- 66 mg/dl, mean of systolic blood pressure was 126.65 +/- 20.85 mmHg and average fasting blood glucose was 116.35 +/- 50.57 mg/dl. Metabolic syndrome was found in 56.21% of the individuals according to IDF criteria. 63.68% of the individuals were under risk for waist circumference and 58.7% and 67.66% of them were under risk in terms of triglyceride values and HDL, respectively. There was not difference between genders and metabolic syndrome (p=.39). There was not difference between the age groups in terms of the presence of metabolic syndrome (p=.37). However, 82.3% of the individuals with metabolic syndrome were aged 50 and over. Conclusion: It was found that individuals were under risk for diabetes, waist circumference, HDL and triglyceride. The prevalence of metabolic syndrome was found to be high in individuals.
Keywords: Metabolic Syndrome; International Diabetes Foundation; Waist Circumference; Diabetes; Triglyceride; ADULT-POPULATION; PREVALENCE; MORTALITY; OBESITY